Pelatihan Dasar Teknologi Informasi Komputer bagi Pelajar Sekolah Dasar - Parmadi, Mokhamad; Haratadi, Ramadhan Dwi Wijaya; Widiyono, Ibnu Prasetyo; Irawan, Yogi Ferdy; Widodo, Puput; Sutopo, Wisnu Guntur; Burhaein, Erick; Azizah, Alfiah Risky; Muhafid, Ervian Arir; Mudayat, Mudayat; Syarif, Ahmad; Sumantri, Riyan Jaya (Abdibaraya, 2023)
One of the tangible manifestations of the Kebumen Nahdhlatul Ulama Ma'arif University (UMNUI) in carrying out community service is the Real Work Lecture (KKN). This Real Work Lecture (KKN) aims to improve students' abilities and insights as a provision for life in the community after graduating from study. In other words, this real work lecture activity is a place for students to help the process of developing villages and communities in the village environment. Based on observations in Kedaleman Wetan Village, Puring District, several problems were found. Seeing these situations and conditions, a KKN work program design was formed as an effort to deal with existing problems. In choosing a KKN work program, there are several things that need to be considered, including the following. 1) Community needs, 2) Knowledge and skills of students, 3) Available time, 4) Facilities and funds, and 5) Natural potential and its inhabitants Keywords: Lectures, Community Service